Students’ decision making in class selection and enrolment - Othman, Muhammad Hanif; Mohamad, Noorihsan; Barom, Mohd Nizam (Emerald Group Publishing Limited, 2019)
Purpose – The purpose of this paper is to propose a theoretical model that integrates various dimensional factors which influence decision-making process of class selection and enrolment, analysing different angles of this process and explaining those factors which determine students’ decision. Design/methodology/approach – This study uses quantitative design to determine and explore students’ decision making in class selection and enrolment. There were 396 students who participated in this study. The data were analysed using principle component analysis to determine the dominant factor for class selection and enrolment. Findings – The study has analysed different factors that can influence students’ decision for class selection and enrolment. Five important underlying factors have been identified which includes the class and lecturer factor, time-space factor, ease and comfort factor, course mate factor and commitment factor. Moreover, the Kruskal–Wallis test shows that there is a significant mean difference in choice and selection behaviour between genders and students’ personal attitudes. Research limitations/implications – This study is an early attempt to explore the wide fields of decision making in class selection and enrolment. It is hoped that follow-up studies would provide more coverage relative to the findings of this research. Practical implications – One particular dimension of micro decision making faced by students is class (course) selection in the beginning of every academic semester/term. Class selection is very critical decision for students as it would reflect students expected outcome for their future career directions. More importantly, the decision made by the students may also affect their academic performance throughout their study. Social implications – From the perspective of the university’s administrators, this issue is very critical for planning purposes. Understanding the students’ behaviour in class selection could improve the cost effectiveness as well as the scheduling of course offering to enhance students’ and instructors’ teaching and learning experience. Originality/value – While many studies try to explore the questions of what makes a student choose a specific college/university or a specific field, limited number have investigated the behaviour of students in class selection and enrolment. This paper contributes to bridging that gap.